2020
DOI: 10.1029/2019jd031685
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Oxidation in the Remote Free Troposphere: Insights From Atmospheric Tomography (ATom)

Abstract: Earth's atmosphere oxidizes the greenhouse gas methane and other gases, thus determining their lifetimes and oxidation products. Much of this oxidation occurs in the remote, relatively clean free troposphere above the planetary boundary layer, where the oxidation chemistry is thought to be much simpler and better understood than it is in urban regions or forests. The NASA airborne Atmospheric Tomography study (ATom) was designed to produce cross sections of the detailed atmospheric composition in the remote at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 63 publications
4
24
0
Order By: Relevance
“…Global models tend to overestimate OH against constraints from methyl chloroform observations ( Shindell et al, 2006 ; Naik et al, 2013 ; Nicely et al, 2017 ), but we find here that tropospheric OH is successfully simulated within observational uncertainty (74% to 135%, 2 σ confidence level). This result from a global CTM is consistent with good agreement between OH measurements and a box model during NASA’s Pacific Exploratory Mission – Tropics (PEM-Tropic B) campaign in the clean remote Pacific ( Tan et al, 2001 ) and a similar analysis by Brune et al (2020) for ATom 1 through 4.…”
Section: Comparison Of Simulated and Measured Ohsupporting
confidence: 82%
See 1 more Smart Citation
“…Global models tend to overestimate OH against constraints from methyl chloroform observations ( Shindell et al, 2006 ; Naik et al, 2013 ; Nicely et al, 2017 ), but we find here that tropospheric OH is successfully simulated within observational uncertainty (74% to 135%, 2 σ confidence level). This result from a global CTM is consistent with good agreement between OH measurements and a box model during NASA’s Pacific Exploratory Mission – Tropics (PEM-Tropic B) campaign in the clean remote Pacific ( Tan et al, 2001 ) and a similar analysis by Brune et al (2020) for ATom 1 through 4.…”
Section: Comparison Of Simulated and Measured Ohsupporting
confidence: 82%
“…Causes of the remote model bias in NO y Figure 8 shows that the model NO y overestimate in winter is primarily caused by nitric acid (HNO 3 ). Excessive remote HNO 3 is a long-standing model deficiency (Bey et al, 2001;Staudt et al, 2003;Brunner et al, 2003Brunner et al, , 2005. The model bias identified here is unlikely to result from overestimated continental emissions due to the short lifetime of NO y against deposition (∼ 3 d in the Northern Hemisphere winter).…”
Section: Constraints On the Remote Source Of Ohmentioning
confidence: 71%
“…Hence, from propagation of error, we estimate that uncertainty (1-σ) in the first source is 32% (considering uncertainties in J O3->O1D as well as in ozone and water vapor measurements reported in the methods section). For radical production due to formaldehyde and HONO photolysis (as well as for radical abundance), at the moment we assume model uncertainty reported in the literature (i.e., Brune et al, 2019 ) of 35%. Likewise, we estimate that uncertainty in other photochemical quantities (radical abundance and ozone production) is similar, but in the future these estimations need to be re-checked as measurements of physical and chemical quantities become available in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…We used the Framework for 0-D Atmospheric Modeling ( Wolfe et al, 2016 ), F0AM v4, which is a complete MATLAB-based software loaded with six ready-to-use atmospheric chemistry mechanisms as well as with three options for resolving photolysis frequencies. The F0AM has been extensively used and proven to be a powerful tool for photochemical simulations (i.e., Brune et al, 2019 ). In the present case, we used the Master Chemical Mechanism ( Jenkin et al, 1997 ; Saunders et al, 2003 ), MCM v3.3.1, obtained via website ( http://mcm.leeds.ac.uk/MCM ).…”
Section: Methodsmentioning
confidence: 99%
“…Willis et al (2016) showed that marine organics contribute to the growth of newly formed particles in the summertime Arctic at low altitude; however, it was unclear if marine organics were involved in nucleation. Burkart et al (2017) found that particle growth in the remote Arctic was largely due to condensation of unidentified organic compounds, possibly of marine origin, associated with oxidation or photochemistry of the sea-surface micro-layer (Abbatt et al, 2019). Andreae et al (2018) proposed that oxidized biogenic volatile organic compounds (VOCs) were the source of recently formed particles found in the outflows and anvils of convective storms over Amazonia.…”
Section: Discussionmentioning
confidence: 99%